Crime, guilt, and punishment : a philosophical introduction - Ten, Chin Liew (Oxford : Clarendon Press ; New York : Oxford University Press, 1987)
A philosophical examination of punishment and criminal responsibility. Discusses the justification of punishment, moral obligations, and alternatives to punishment such as treatment.
Includes topics on moral justification of punishment, criminal responsibility, mental illness, legal excuses, utilitarianism, and retributive justice.
Includes bibliographical references and index.
Keywords: Criminal Law